The Effect of Time Management and Communication on Employee Performance with Mediation of Work Motivation in The Kepeng Money Crafts Industry, Kamasan Village, Klungkung District - Made Ermawan Yoga Antara; Ni Wayan Sitiari; Wayan Gde Sarmawa (Jurnal Ekonomi & Bisnis JAGADITHA, 2021)
One of the efforts to improve employee performance is through improvements in time management and communication within the organization. The increasing of time management and communication is expected to increase work motivation for employees. The increasing of employee’s motivation is also expected to have an impact on improving the performance of the employees themselves. This study aims to examine the employee performance through time management, communication and work motivation that was conducted at the Kepeng Money Craft Industry in Kamasan Village, Klungkung District, which involving all 40 company employees as research respondents. This research was conducted in a census. The distribution of questionnaire to the respondents is the method used in collecting the data, then the data is processed using the Structural Equation Modeling Partial Least Square (PLS) method, through the SmartPLS 3.0 program, at a significance level of 0.05 (5%). The results of this study found that time management, communication, and work motivation each had a positive and significant effect on employee performance. Time management has a significant positive effect on work motivation. Time management has a significant positive effect on employee performance. Communication has a significant positive effect on work motivation. Communication has a significant positive effect on employee performance. Work motivation has a significant positive effect on employee performance. Work motivation mediates some of the effects of time management on employee performance. Work motivation mediates some of the effects of communication on the performance of employees of the kepeng handicraft industry in Kamasan Village, Klungkung Regency.